Eksistensi Kelembagaan Ulama Perempuan di Nusa Tenggara Barat - Jumarim Jumarim (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This study aims to map the forms, strategies and impacts of social roles that have been carried out by PW Muslimat NU NTB and PW Aisyiyyah NTB. The data collection methods in this study were intensive observation, in-depth interviews and documentation. The process of data analysis in this study will be carried out in an on-going process in the field, so that it is easy to dig up missing data or confirm data that is still unclear. The results of the study show that the social roles that have been carried out by PW Muslimat NU NTB and PW Aisyiyyah NTB in gender inequality and injustice in NTB at this time can at least be reduced due to the hard work of Aisyiah and Muslimat NU with other groups, for example with almost equal education participation rates. between men and women at the SD/MI, SMP/MTS and SMA/SMK levels, even to the tertiary level. The consistency and continuity of the Aisyiah and Muslimat NU movements in boosting the dignity of women in NTB is something more than these two organizations compared to women's organizations that fall into the category of NGOs and NGOs which tend to be programmatic, casuistic and highly dependent on donors. Even the institutional pattern of NGO women's groups continues to change according to the